2022
DOI: 10.1021/acscatal.1c05351
|View full text |Cite
|
Sign up to set email alerts
|

An Alternative Proposal for the Reaction Mechanism of Light-Dependent Protochlorophyllide Oxidoreductase

Abstract: Light-dependent protochlorophyllide oxidoreductase is one of the few known enzymes that require a quantum of light to start their catalytic cycle. Upon excitation, it uses NADPH to reduce the C 17 −C 18 in its substrate (protochlorophyllide) through a complex mechanism that has heretofore eluded precise determination. Isotopic labeling experiments have shown that the hydride-transfer step is very fast, with a small barrier close to 9 kcal mol −1 , and is followed by a proton-transfer step, which has been postu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 81 publications
0
22
0
Order By: Relevance
“…An alternative mechanism for POR was proposed during the reviewing process for this manuscript, which involves eT from Tyr193 to the photoactivated PChlide . This mechanism was calculated to have a lower barrier (Δ G ‡ = 46.4 kJ mol –1 ), but a redox active Tyr193 is not consistent with mutagenesis experiments, which have shown that while Tyr193 mutants show decreased activity at physiological temperatures, there is no significant difference in the rate of HYT in the Y193F variant at cryogenic temperatures compared to that in the wild type .…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…An alternative mechanism for POR was proposed during the reviewing process for this manuscript, which involves eT from Tyr193 to the photoactivated PChlide . This mechanism was calculated to have a lower barrier (Δ G ‡ = 46.4 kJ mol –1 ), but a redox active Tyr193 is not consistent with mutagenesis experiments, which have shown that while Tyr193 mutants show decreased activity at physiological temperatures, there is no significant difference in the rate of HYT in the Y193F variant at cryogenic temperatures compared to that in the wild type .…”
Section: Resultsmentioning
confidence: 93%
“…Such a conformational change is likely required prior to protonation, yet it is not clear at what point during the reaction this occurs. Note, however, that protonation might involve bridging water molecule(s), and other proton donors have also been proposed based on alternative PChlide binding poses, , although Tyr193 is the most likely proton donor in our published model . All calculations were performed in Gaussian 16 revision A03 .…”
Section: Computational Methodsmentioning
confidence: 99%
“…The run using umbrella sampling (US) methodology on molecule 6 was carried out employing the YASARA macro written by Silva ( , accessed on 28 February 2023) [ 58 ].…”
Section: Methodsmentioning
confidence: 99%
“…Cys309 is fully conserved throughout all POR enzymes and interestingly, when the equivalent residue in T. elongatus POR, Cys226, was previously mutated to a Ser residue it appeared to influence the hydride and proton transfer chemistry [23]. To complicate matters further, a recent computational study suggested yet another alternative mechanism [11]. In this scenario, Pchlide photochemistry leads to electron transfer from the conserved Tyr residue to the C18 position of Pchlide, followed by a subsequent proton transfer, also from the Tyr residue, then electron and hydride transfer from NADPH [11].…”
Section: Introductionmentioning
confidence: 99%